The simulation of volume shrinkage for double-injection molding with PC and ABS - Leklong, Pichai; Sriseubsai, Wipoo (My University, 2018)
The objective of this paper was to study and analyze the plastic injection molding parameters to reduce the volume shrinkage of double injection molded part. The specimen was molded with Acrylonitrile-butadiene-styrene (ABS) after Polycarbonate was molded as a half part. The weld line occurred at the haft of the molded part. The simulation with Moldex 3D R13 and the design of experiment with Taguchi method was used to perform the experiments and analyze the data to get the optimum of volume shrinkage. The results showed that melt temperature and packing pressure was significant to the volume shrinkage. When using low melt temperature and high packing pressure, the shrinkage was low and related to the thermal expansion of the material. It would be one of the parameters to the design of double injection molding.